Islamicpreneurship sebagai strategi penguatan kewirausahaan berbasis nilai islam di era ekonomi digital - Sholihah, Nailatus (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the concept of Islamicpreneurship as an entrepreneurship model based on Islamic values that is relevant in the digital economy era. Islamicpreneurship is an integration of business activities and sharia principles emphasizing honesty, trustworthiness, justice, responsibility, and blessing-oriented goals. This research employed a descriptive qualitative approach through library research by examining various scientific literatures related to Islamic entrepreneurship, sharia business ethics, and modern business challenges. The findings indicate that Islamicpreneurship has significant potential to create an ethical, sustainable, and competitive business ecosystem. However, its implementation still faces obstacles such as low Islamic financial literacy, limited access to financing, unhealthy market competition, and insufficient understanding of contracts in digital transactions. On the other hand, digital technology development provides new opportunities for Muslim entrepreneurs to expand markets through e-commerce, digital marketing, and halal-based service innovation. Therefore, strengthening Islamicpreneurship requires support from Islamic entrepreneurship education, government policies, stronger Islamic financial institutions, and collaboration among business actors. This study confirms that Islamicpreneurship is not merely an economic concept but a business paradigm balancing material profit with spiritual values and social benefits.